Empowering Introvert Students: How Artificial Intelligence Applications Enhance Speaking Ability - Liya Astarilla Dede Warman; Susi Erlinda; Tashid Tashid; Karpen Karpen; T Sy Eiva Fatdha (STAI Hubbulwathan Duri, 2023)
The rapid development of technology has increased the use of Artificial Intelligence (hereafter, AI) applications to improve students’ English skills, especially in speaking skill. This study aimed to investigate the effectiveness of AI applications to improve the introvert students’ speaking ability. Pre-experimental one group pre-test and post-test design was utilized in this study. This study conducted with 85 introvert students from two universities in Riau, Indonesia chosen by using MBTI test and purposive sampling technique. The data were collected through the questionnaire and speaking test. The data were analyzed by using SPSS 25th version to find out the descriptive statistic, normality test, and paired sample t-test. This finding shed light AI applications were effective in improving the introvert students’ speaking ability. It was proved that the t-test was higher than the t-table value (12.8231.663) with the level of significance p0.05. In short, there was significant difference on the students’ speaking ability before and after using AI applications for English speaking practiced. In conclusion, AI applications can be implemented to improve university students’ speaking ability.